Radio Programme on how to Identify and Control Major Cassava Diseases on your Farm - Mubiru, Wasswa (Technical Centre for Agricultural and Rural Cooperation, 2008)
Many plant diseases are caused by very tiny living things called pathogens. Pathogens are so tiny that you cannot see them even with a naked eye. Examples of pathogens are viruses, bacteria, and fungi. When a pathogen attacks a cassava plant, it multiplies and spreads inside or on the plant. As it spreads, it destroys the plant. The plant will show signs (symptoms) of attack. Damage symptoms of major cassava diseases appear on the leaves, stems, and storage roots or tubers of the plant. Cassava diseases are recognized by their symptoms, such as discoloration of leaves, ?sores? on the stems, and discoloration of storage roots.Some other diseases which you may notice in cassava are caused by non living things. Examples of such diseases are wilting due to drought and poor plant growth because of poor soils.